Infancia, educación y producción de subjetividad: el fenómeno “youtuber niño/niña” en Brasil - Derkoski Dalla Nora, Heloísa; Cadoná, Eliane (Universidad de Costa Rica, 2024)
In this article we discuss, based on social constructionism and gender studies, how the media works as a tool that educates the childhood and produces ways of being, thinking and acting. The main objective of the study was to problematize meanings of motherhood and childhood broadcasted on Youtube, through advertising for chilldren’s toys and games. This is a qualitative, descriptive, documental research, composed of sixteen videos by brazilian youtuber Valentina Pontes, that was analysed using the Discourse Analysis. We will bring here the discussions of the axis "The representation of maternity in the media: from the infantized mother to the girl mother",and invites to problematizations about the construction of maternity from the media point of view, and its influence on the production of subjectivity in childhood. We discuss, first, what is the image that Erlânia, Valentina’s mother, represents: a maternity that renounces her identity in favor of the care of the children. The second image of a mother found is Valentina herself, encourage, by a series of devices, to play as a mother. This role, by speeches and moments of fun, reinforces the deterministic idea that, for woman motherhood is something natural in the course of life. It is possible to say that Pontes family is one of the producer of many Brazilian childhoods. An example of this is the channel’s wide audience, which gives Valentina a prominent place among Youtubers, a fact that, possibly, not only impacts desires, truths and perspectives of others families, but also reinforces what they believe to be an ideal way of childhood and motherhood.